Pengaruh Pendalaman Iman APP 2024 Terhadap Kehidupan Mahasiswa STP IPI Malang - Fabiana Christa Natalia; Intansakti Pius X (International Forum of Researchers and Lecturers, 2024)
This paper discusses the influence of deepening the faith of the 2024 Development Fasting Action (APP) on the lives of STP IPI Malang students. This research uses descriptive qualitative methods with observation as a data collection technique. The results of the research show that APP 2024 faith deepening has not been implemented well at STP IPI Malang. This can be seen from the large number of students who have not been involved in this implementation, either as officers or as participants. There are several factors that cause this to happen, including students being busy and students' lack of interest in deepening their faith. The impact of the implementation of APP 2024's faith deepening is not yet achieving the expected goals, namely increasing student awareness of social problems and helping people in need. Based on the results of this research, the author suggests that the STP IPI Malang faith deepening committee be more aggressive in socializing the APP faith deepening program to students. Apart from that, the STP IPI Malang faith deepening committee also needs to find ways to increase students' interest in this faith deepening.